1997
DOI: 10.1017/s0022149x00015819
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cadmium on the immune behaviour of guinea pigs with experimental ascariasis

Abstract: The subchronic effect of cadmium on selected immunological parameters was studied in guinea pigs with experimental ascariasis. Cadmium chloride given orally for 28 days caused a considerable suppression of T- and B- cells in the lymphoid organs of intoxicated animals, of the metabolic activity of their peritoneal macrophages and a moderate decline in the level of complement CH50 and AH50 from day 1 to day 28 of the experiment, in comparison with the initial value. After a subsequent infection of the subchronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Moreover, this effect was found to persist up to 3 weeks after removal of pesticides in the 10-exposed frogs (Christin et al, in press). Similarly, depression of lymphocyte proliferation was detected in guinea pigs exposed to heavy metal toxicants, resulting in an enhanced abundance of migrating Ascaris suum in the lungs (Boroskova et al 1995;Boroskova and Dvoroznakova 1997;Soltys et al 1997). It is well established that lymphocytes play a determining role in the generation of an effective immune response against helminth parasites (Riffkin et al 1996;Schallig 2000).…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, this effect was found to persist up to 3 weeks after removal of pesticides in the 10-exposed frogs (Christin et al, in press). Similarly, depression of lymphocyte proliferation was detected in guinea pigs exposed to heavy metal toxicants, resulting in an enhanced abundance of migrating Ascaris suum in the lungs (Boroskova et al 1995;Boroskova and Dvoroznakova 1997;Soltys et al 1997). It is well established that lymphocytes play a determining role in the generation of an effective immune response against helminth parasites (Riffkin et al 1996;Schallig 2000).…”
Section: Discussionmentioning
confidence: 93%
“…The expression of eight C. elegans C-type lectin genes were affected by cadmium. There are several reports describing a relationship between cadmium exposure and changes in the immune response [ 40 , 41 ]. The immune response genes may be affected by cadmium due to the modulation of shared signal transduction pathways, such as the MAPK signaling cascade [ 27 , 42 - 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given both evidence for copper's antiparasitic activity [138] and evidence that copper increases host immunity [139], it is not surprising that results have shown that pure copper salts reduce GI nematode worm burdens in chickens infected with Ascaridia galli [38]; in dairy goats infected with Haemonchus but not T. circumcincta, Trichostrongylus colubriformis, or Oesophagostomum venulosum [140]; in guinea pigs infected with Ascaris [141]; and in lambs [142,143] with ostertagiasis. It has also been shown that basic salts were more effective than neutral salts against A. galli and the authors suggested that this occurred because resorption of basic salts by the host is lower compared with neutral salts and this prolongs their antiparasitic action on intestinal nematodes [144À146].…”
Section: Coppermentioning
confidence: 99%
“…In another set of studies, concurrent administration of copper with the heavy metal mercury to Ascaris-infected guinea pigs failed to produce the same immunosuppression as occurred when mercury chloride was given alone; these authors had suggested that cupric sulphate would have a protective effect preventing the decline in antibody production. However, the concurrent administration of the metal elements provided no additional protective effect of copper against the negative effect of mercury on macrophages and PHM leucocytes [141,147,148], showing that both elements can become toxic at high levels and that the known protective effect of copper may be exceeded.…”
Section: Combined Trace Elementsmentioning
confidence: 99%